2013
DOI: 10.1002/pnp.289
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatments for ADHD

Abstract: In the second of this series of updated reviews on the major psychiatric drug groups, in association with the College of Mental Health Pharmacy (CMHP; www.cmhp.org.uk), Caroline Parker discusses the use of drug treatments in the management of attention deficit hyperactivity disorder (ADHD), including their indications, efficacy, adverse effects and recommended dosing regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…24 Some studies have shown that response rates and symptom improvement seen with atomoxetine are similar to those associated with psychostimulants, 20,25 though some show a lesser effect. 20 Treatments should be titrated upwards according to individual needs until no further improvement is noted and side-effects are tolerable.…”
Section: Psychological Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…24 Some studies have shown that response rates and symptom improvement seen with atomoxetine are similar to those associated with psychostimulants, 20,25 though some show a lesser effect. 20 Treatments should be titrated upwards according to individual needs until no further improvement is noted and side-effects are tolerable.…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…18 Rash and pruritis may warrant discontinuation if severe and do not settle. 24 Patients are not always aware that psychiatric sideeffects may be medication related. 18 Symptoms of psychosis, mania, panic attacks and violent behaviour should be reported urgently with a view to dose reduction or cessation.…”
Section: Psychological Interventionsmentioning
confidence: 99%
See 3 more Smart Citations